(untitled) (Research, Society and Development, 2022)
Study with the objective of tracing the profile of diabetic pregnant women. Observational, cross-sectional descriptive research, through a non-probabilistic sample consisting of diabetic pregnant women who were admitted to a public Maternity Hospital in the city of Rio de Janeiro, from September to December 2021. The variables demographic, social and economic characteristics; pregnancy characteristics and health problem characteristics were collected through a questionnaire applied face to face. Study participants ranged in age from 20 to 50 years old, were in the third trimester of pregnancy, brown, and sedentary. They were predominantly unplanned pregnancies, with an average of three pregnancies per woman. Most of them have a high school education and are inserted in the labor market. There was a prevalence of diabetes diagnosed during pregnancy, a significant number of hypertension associated, a higher number of women using insulin; a past history of hospitalization during pregnancy, with diabetes as the main cause. All of them said they monitored their blood glucose levels using a glucometer, and most of them received guidance on diabetes during pregnancy, and those who use insulin received instruction on how to prepare and apply the drug. All of them have a cell phone and most have access to the Internet at home through mobile data and Wi-Fi network.